(untitled) (MATEMATIKA, 2021)
The integration of economic and social objectives is essential for Islamic bank to stimulate economic growth through the effective management and allocation of wealth and resources. This article proposes a hybrid mathematical optimization between the analytic hierarchy process (AHP) and multi-choice goal programming (MCGP) methods. The hybrid methods make the amalgamation of economic and social objectives possible in the multi-objective model of Islamic banking. The AHP method is used to determine the priorities or weights on each of the economic and social objectives. MCGP on the other hand, serves as an optimizer to the Multi-objective Decision Making (MODM) model that fits the priorities to the objectives and possible target goals. Results confirmed on the practicality and flexibility of the hybrid AHP-MCGP model which enable Islamic banks to better utilize their financial resources based on the priorities and multiple target goals. The feasible achievement of multi-objective with an interval target goal has offered the avenue for the decision makers at Islamic bank to satisfy economic and social goals simultaneously.